2013
DOI: 10.1111/jan.12076
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to living with a mechanical aortic heart valve: a phenomenographic study

Abstract: The oral anticoagulation therapy was considered the most troublesome consequence, but also the sound of the valve was difficult to accept. Patient counselling and adequate follow-up can make patients with mechanical aortic heart valves more confident and competent to manage their own health. We recommend that patients should participate in a rehabilitation programme following cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
0
19
0
3
Order By: Relevance
“…Al considerar evitar una reintervención en los pacientes de menos edad, se olvidan frecuentemente los aspectos que afectan el día a día del individuo. Por un lado, la anticoagulación es de por vida y la predisposición al sangrado favorecida por estos fármacos puede eventualmente hacer necesario el uso de protectores para desempeñar actividades de la vida diaria o modificar el atuendo para no exponer áreas de equimosis (41) .…”
Section: Válvulas Mecánicas Y Su Impacto En La Calidad De Vidaunclassified
See 1 more Smart Citation
“…Al considerar evitar una reintervención en los pacientes de menos edad, se olvidan frecuentemente los aspectos que afectan el día a día del individuo. Por un lado, la anticoagulación es de por vida y la predisposición al sangrado favorecida por estos fármacos puede eventualmente hacer necesario el uso de protectores para desempeñar actividades de la vida diaria o modificar el atuendo para no exponer áreas de equimosis (41) .…”
Section: Válvulas Mecánicas Y Su Impacto En La Calidad De Vidaunclassified
“…Por otro lado, la presencia permanente de un click audible puede constituirse en un problema (41) . Cuestionarios sobre calidad de vida han señalado este aspecto como uno de los más relevantes.…”
Section: Válvulas Mecánicas Y Su Impacto En La Calidad De Vidaunclassified
“…Two qualitative studies investigated the later recovery period and follow-up among patients undergoing heart valve surgery. An interview study by Oterhals et al (2013) among 20 patients undergoing aortic valve replacement with mechanical prosthesis during 10 years found that patients moved between four ways of adapting to living with a mechanical heart valve following surgery; 'the competent patient' wanted to stay in control of his or her life; 'the adjusted patient' considered the implications of having a mechanical aortic valve as part of daily life; 'the unaware patient' was not aware of interactions between warfarin, diet and medication and 'the worried patient' was bothered by the oral anticoagulation and annoyed by the sound of the valve. Berg et al (2013) interviewed 10 patients once 6-9 months after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…While some researchers note that a phenomenographic study should include twenty participants to be able to obtain different understandings according to the actual phenomenon under study (24,25), others claim that this approach does not prescribe any specific sample size (43). In the present study, the last interviews did not contribute to any further information regarding the midwives' understanding of their work.…”
Section: Limitationsmentioning
confidence: 99%
“…They were recruited by phone calls to AMUs (n=5) and FMUs (n=5) with at least 100 births/year, and further in accordance with strategic sampling (24). We presented our purpose for calling to the midwife (not necessarily a leader), answering the phone and asked if she could assist in approaching midwives working in the AMU/FMU.…”
Section: Participantsmentioning
confidence: 99%